2015
DOI: 10.1111/head.12601
|View full text |Cite
|
Sign up to set email alerts
|

Triptans in the Acute Treatment of Migraine: A Systematic Review and Network Meta‐Analysis

Abstract: Background.-Although triptans are widely used in the acute management of migraine, there is uncertainty around the comparative efficacy of triptans among each other and vs non-triptan migraine treatments. We conducted systematic reviews and network meta-analyses to compare the relative efficacy of triptans (alone or in combination with other drugs) for acute treatment of migraines compared with other triptan agents, non-steroidal anti-inflammatory drugs (NSAIDs), acetylsalicylic acid (ASA), acetaminophen, ergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
197
0
17

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(221 citation statements)
references
References 28 publications
7
197
0
17
Order By: Relevance
“…Triptan ve NSAİİ kombinasyon tedavisinin sınandığı bir çok çalışma bu sonucu desteklemektedir. [11][12][13] Migren serebral korteks, beyin sapı, PAG, aminerjik nukleuslar, yüksek servikal duyu nöronları ve trigeminovasküler sistemin çok yönlü etkileşimleriyle oluşur. [14] Periferik duyarlılaşma sonucu trigeminovasküler sistem aktivasyonu ve meninkslerde nöroje-nik enflamasyon oluşur.…”
Section: Discussionunclassified
“…Triptan ve NSAİİ kombinasyon tedavisinin sınandığı bir çok çalışma bu sonucu desteklemektedir. [11][12][13] Migren serebral korteks, beyin sapı, PAG, aminerjik nukleuslar, yüksek servikal duyu nöronları ve trigeminovasküler sistemin çok yönlü etkileşimleriyle oluşur. [14] Periferik duyarlılaşma sonucu trigeminovasküler sistem aktivasyonu ve meninkslerde nöroje-nik enflamasyon oluşur.…”
Section: Discussionunclassified
“…Considering the outcome headache-free response at 2 hours, triptan standard doses gave better results than ergot's (42-76% and 38% response, respectively) and equal or better responses than NSAIDs, aspirin and acetaminophen [Cameron et al 2015;Diener et al 2002]. Moreover, eletriptan tablets, together with sumatriptan subcutaneous injection and rizatriptan and zolmitriptan, showed the most favorable responses among all triptans [Cameron et al 2015]. Compared with zolmitriptan, eletriptan 80 mg, but not 40 mg, showed significant superiority when considering the 2-hour headache-response outcome.…”
Section: Eletriptan: Efficacy In Head-to-head Studiesmentioning
confidence: 93%
“…A recent systematic review and network metaanalysis of 133 randomized controlled trials that compared triptans with placebo-controlled or active migraine treatments showed that triptan standard doses provided a headache-free response in 42-76% of patients and a sustained headachefree response in 29-50% of patients with a rescuemedication-use rate of about 27% [Cameron et al 2015]. Considering the outcome headache-free response at 2 hours, triptan standard doses gave better results than ergot's (42-76% and 38% response, respectively) and equal or better responses than NSAIDs, aspirin and acetaminophen [Cameron et al 2015;Diener et al 2002].…”
Section: Eletriptan: Efficacy In Head-to-head Studiesmentioning
confidence: 99%
“…Cameron and colleagues conducted a systemic review and network meta-analysis comparing the relative efficacy of triptans using the Cochrane Library, Medline and Embase (133 randomised trials). 14 The main efficacy variables (headache relief within 2 hours, 2-hour sustained freedom from pain, sustained headache relief and freedom from pain at 24 hours) were met by standard doses of triptans with rates from 18-76% of patients.…”
Section: Serotonin Syndromementioning
confidence: 98%
“…Generally, triptans provided equal or better outcomes than other migraine treatments but slightly worse efficacy than combination therapy. 14 This review examines the use of the currently licensed triptans for the treatment of acute migraine and practical considerations when selecting a triptan for this indication. The efficacy and safety of the triptans using data from clinical trials and real-world studies will be compared.…”
mentioning
confidence: 99%